Cover Picture: Photochemical Transformations Accelerated in Continuous‐Flow Reactors: Basic Concepts and Applications / Low‐LUMO Pyrene‐Fused Azaacenes / Synthesis, Characterization, and Metal Ion Coordination of a Multichromophoric Highly Luminescent Polysulfurated Pyrene / Indirect Photochemistry in Sunlit Surface Waters: Photoinduced Production of Reactive Transient Species / Carbon Monoxide‐Induced Dynamic Metal‐Surface Nanostructuring / Biomimetic Synthesis of (+)‐Ledene, (+)‐Viridiflorol, (−)‐Palustrol, (+)‐Spathulenol, and Psiguadial A, C, and D via the Platform Terpene (+)‐Bicyclogermacrene / Molecular Chalcoxides (ChalcoPolyoxometalates): A Family of Functional Materials with Emergent Properties / A SIM‐MOF: Three‐Dimensional Organisation of Single‐Ion Magnets with Anion‐Exchange Capabilities (Chem. Eur. J. 34/2014). Issue 34 (18th August 2014) - Su, Yuanhai; Straathof, Natan J. W.; Hessel, Volker; Noël, Timothy; More, Sandeep; Bhosale, Rajesh; Mateo‐Alonso, Aurelio; Fermi, Andrea; Ceroni, Paola; Roy, Myriam; Gingras, Marc; Bergamini, Giacomo; et al.
<x xml:space="preserve">Abstract</x> The Young Chemists Special Issue has been put together to celebrate the past winners of the European Young Chemist Award (EYCA), presented at the first four EuCheMS Congresses, and to highlight the great diversity of research currently being conducted by young chemists from all over the world. Nine manuscripts that highlight this diversity have been selected to feature in the cover picture. In the top row from left to right: T. Noël et al. (p. 10562 ff.), A. Mateo‐Alonso et al. (p. 10626 ff.), and M. Gingras, G. Bergamini et al. (p. 10661 ff.). In the middle row from left to right: D. Vione et al. (p. 10590 ff.), S. Carenco (p. 10616 ff.), and N. Cramer et al. (p. 10654 ff.). In the bottom row from left to right: H. N. Miras (p. 10554 ff.), A. Tavassoli et al. (p. 10608 ff.), and E. Coronado, G. Mínguez Espallargas et al. (p. 10695 ff.).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>